Development of Interactive Media for ICT Learning at Elementary School Based on Student Self Learning - Sri Huning Anwariningsih; Sri Ernawati (Intelektual Pustaka Media Utama, 2013)
The implementation of information and comunication technology (ICT) curriculum at elementary school is the educational sector development. ICT subject is a practical subject which require a direct practice to make easier in the student understanding. Therefore, a teacher is demanded to make a learning media which helps the student to understand the material of study. This research is aimed at describing the model of ICT study in elementary school and using of learning media. Moreover, the description can be bocome one of the basic from the development of interactive study model base on student self learning. Besides, the arraging of this study model is hoped to make habitual and self learning.